"To silence the deafening silence": Survivor's needs and experiences of the impact of disaster radio for their recovery after a natural disaster. (September 2016) - Hugelius, Karin; Gifford, Mervyn; Ortenwall, Per; Adolfsson, Annsofie
Highlights: Disaster radio offers a way to communicate with disaster survivors. Disaster radio is a positive contribution to the survivors' recovery after disasters. Both information and music contributed to recovery among the survivors. More research of disaster radio as a health recovery intervention is suggested. Abstract: In the aftermath of the Haiyan typhoon, disaster radio was used to spread information and music to the affected population. The study described survivors' experiences of being in the immediate aftermath of a natural disaster and the impact disaster radio made on recovery from the perspective of the individuals affected. Twenty eight survivors were interviewed in focus groups and individual interviews analyzed with phenomenological-hermeneutic method. Being in disaster mode included physical and psychosocial dimensions of being in the immediate aftermath of the disaster. Several needs among the survivors were expressed. Disaster radio contributed to recovery by providing facts and information that helped the survivor to understand and adapt. The music played contributed to emotional endurance and reduced feelings of loneliness. To re-establish social contacts, other interventions are needed . Disaster radio is a positive contribution to the promotion of survivors' recovery after disasters involving a large number of affected people and severely damaged infrastructure. Further studies on the use and impact of disaster radio are needed.